Robust Boolean operations algorithm on regularized triangular mesh and implementation - Wang, Hongjuan; Kan, Shuting; Zhang, Xingli; Lu, Xinming; Zhou, Longquan (Multimedia tools and applications, 2020)
Boolean operations are an essential tool for creating complex entities in many fields. In order to implement complex entity modeling, we proposed a method based on robust Boolean operations that focused on the robustness of geometric calculations caused by computational errors and data error. This method used a uniform logical judgment to analyze the specific conditions of the intersection of vertices or edges in advance, and avoided the inconsistency between logical judgment results and geometric relations. We correspondingly obtained the positions of the two triangles, the validity of the intersection and the intersection edges from tetrahedral-volume calculations, the triangle-area calculations, and the topology information to mark the triangles instead of intersecting lines tracking and the judgment of the triangles inside the entities. Finally, the experimental results indicate that this method realized the three-dimensional modeling of any complex geological body.